Challenger : a true story of heroism and disaster on the edge of space [compact disc, unabridged] - Higginbotham, Adam (Simon & Schuster Audio, 2024)
From the New York Times bestselling author of Midnight in Chernobyl comes the definitive, dramatic, minute-by-minute story of the Challenger disaster based on fascinating new archival research and in-depth reporting, a riveting history that reads like a thriller.